Educational Change Process at an Elementary School of the Arts - María Teresa Muñoz Quezada (Universidad Autónoma de Baja California, 2009)
This article presents a qualitative research conducted at a municipal school in the South of Chile. The education change process at said institution is described and interpreted based on the growth and stability of the school, product of the new and definitive infrastructure acquisition. Results show how directors, professors, representatives and students live the process differently. The fear for reconstructing a new identity, the desire for recovering the school's ethos as well as professors, representatives, new and older student's conflicts were observed, apart from the search for the conciliation between the modern world demands and the educational project.